Camera-based security system application at Perumahan Taman Embong Anyar 1, Dau District, Malang - Moch. Syamsul Ma'arif; Sugiarto Sugiarto; Erwin Sulistyo (Universitas Muhammadiyah Magelang, 2023)
At Taman Embong Anyar 1 Housing Complex in Dau District, Malang, there is a high crime risk due to residents' activity patterns and open access to residential areas. One of the community's biggest issues is a lack of understanding of using security technology. As an alternative to monitoring the situation in residential areas, CCTV installation and operation assistance are needed to increase environmental security. Beginning with a survey of the areas where CCTV must be installed, the CCTV system must then be selected, installed, and its operation explained to all users. The residents can use and maintain the CCTV system as a result of the entire series of activities. The environment is made more secure and the workload of security officers is minimized with the installation of CCTV.